Qualitative Study: Comparison of Implementation of The Effectiveness of the Ethno-Religious-Based SAVI Model in Improving Problem-Solving Skills in PAI Learning - Amiruddin Abdullah; Ari Wijayanti; Wiwid Suryono; Marita Ika Joesidawati; Ahamd Zain Sarnoto; Siti Fatimah Hiola; Aat Ruchiat Nugraha; Windy Dian Sari; Sukini Sukini; Tomi Apra Santosa (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to determine the effectiveness of the Ethno-Religious-based SAVI model on students' problem-solving ability in PAI learning meta-analysis.Â  The eligibility criteria in this study are a) research data obtained from the Google Scholar database, ProQuest, ERIC and Wiley, b) The research must be indexed by the Science Technology Index (SINTA), Scopus and Wos, c) The research topic must be relevant, d) the research is published in the 2020-2023 range, d) the publication must have a score of (r), (t) or F, e) the level of education of the participants, namely elementary, junior high and high school and the sample size of this research > 30 students.Â  Data analysis with the help of JSAP 0.8.5 application. The results of this study are 1) 18 studies analyzed are heterogeneous and normal, 2) there is an influence of ethno-religious-based SAVI model on students' problem-solving ability in PAI learning with a high effect size category (p < 0.001 ; rRE = 1.12 and 3) in this study there is no publicity bias. These findings provide information that the ethno-religious-based SAVI model is effective in improving students' problem-solving skills in PAI learning.